ENGLISH AND UZBEK STORYTELLING (Ustozlar uchun, 2025)
This annotation summarizes a comparative analysis of English and Uzbek storytelling. The article explores their historical development, thematic diversity, stylistic features, and character representation. It highlights that English storytelling is characterized by psychological depth, individualism, and analytical narrative techniques, while Uzbek storytelling emphasizes national values, emotional expression, and culturally rooted imagery. The study provides insights into both literatures and enhances understanding of their artistic significance.